2010
DOI: 10.1029/2009gl041735
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in extreme winds predicts large wildfire locations in chaparral ecosystems

Abstract: [1] Fire plays a crucial role in many ecosystems, and a better understanding of different controls on fire activity is needed. Here we analyze spatial variation in fire danger during episodic wind events in coastal southern California, a densely populated Mediterranean-climate region. By reconstructing almost a decade of fire weather patterns through detailed simulations of Santa Ana winds, we produced the first high-resolution map of where these hot, dry winds are consistently most severe and which areas are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
133
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 22 publications
(27 reference statements)
10
133
2
Order By: Relevance
“…Fire occurrence is favoured by low humidity and high temperature, whereas wind speed has long been recognised as the crucial factor influencing the rate of spread of wildfires (Rothermel 1972;Fosberg 1978). In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c.…”
Section: Discussionmentioning
confidence: 99%
“…Fire occurrence is favoured by low humidity and high temperature, whereas wind speed has long been recognised as the crucial factor influencing the rate of spread of wildfires (Rothermel 1972;Fosberg 1978). In addition, interactions of fuels and weather with local topography can greatly influence fire activity (Moritz et al 2010;Sharples et al 2012). Fire behaviour models incorporate information on fuels, topography and weather to predict fire spread (Sullivan 2009a(Sullivan , 2009b(Sullivan , 2009c.…”
Section: Discussionmentioning
confidence: 99%
“…Thus a higher selectivity towards flammable fuels would be expected. Extreme fire weather could produce large wildfires whose spread is not determined by landscape structure (Salvador et al, 2005;Moritz et al, 2010). In the past the situation may have been different.…”
Section: Fire Weather Is More Important Than Landscape Pattern In Detmentioning
confidence: 99%
“…Piñol et al, 1998;Good et al, 2008). However, other studies have shown that extreme fire weather could produce large fires whose spread is not determined by landscape structure (Salvador et al, 2005;Moritz et al, 2010). In this respect, the area burnt per fire event (AB) in relation to the FWI was calculated for each sub-region (not shown).…”
Section: Fwi Validationmentioning
confidence: 99%